Strategi Pemasaran Digital untuk UMKM di Era Digital - Ainil Mardiah; Sunarni; Nia Rifanda Putri; Mohammad Gifari Sono; Johni Eka Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this modern era, the development of the industrial and business world is growing rapidly. This causes business owners to have to compete with tight competition. One of the problems that makes the competitiveness of MSMEs still low is the limited ability of business actors in marketing. The research method used in the Digital Marketing Strategy study for MSMEs in the Digital Era is a qualitative method. This research was conducted through a series of qualitative interviews with MSME actors. The results of the study show that MSME actors who implement digital marketing get higher sales. Therefore, digital marketing strategies can be an effective solution for MSMEs in increasing their sales. In addition, this article also states that marketing strategies in the digital era are not only aimed at achieving sales targets, but also to increase awareness and branding of the business itself.